The Mediating Effect of Organisational Sustainability and Employee Behaviour on the Relationship between GHRM and Sustainable Performance in Qatar - Alenzi M.A.S.; Jaaffar A.H.; Khudari M. (World Scientific and Engineering Academy and Society, 2023)
-This study examined the influence of green human resource management (GHRM) practices on Sustainable Performance (SP) and how GHRM practices can help organizations improve their EP through Organisational Sustainability (OS) and Employee Behaviour (EB). T